2014
DOI: 10.1186/1476-4598-13-119
|View full text |Cite
|
Sign up to set email alerts
|

GAS5 long non-coding RNA in malignant pleural mesothelioma

Abstract: BackgroundMalignant pleural mesothelioma (MPM) is an aggressive cancer with short overall survival. Long non-coding RNAs (lncRNA) are a class of RNAs more than 200 nucleotides long that do not code for protein and are part of the 90% of the human genome that is transcribed. Earlier experimental studies in mice showed GAS5 (growth arrest specific transcript 5) gene deletion in asbestos driven mesothelioma. GAS5 encodes for a lncRNA whose function is not well known, but it has been shown to act as glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 52 publications
(80 reference statements)
6
57
0
Order By: Relevance
“…We hypothesize that accumulation of GAS5 in the nucleus may be one of crucial processes of exerting its function. In additon, Renganathan et al revealed that GAS5 is slightly more abundant in the nucleus than that in the cytoplasm in the absence of HhAntag and prevalence in the nucleus was examined after treatment with HhAntag, indicating that HhAntag-induced growth arrest involves accumulation of nuclear GAS5 (18). This study reinforced our hypothesized model.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We hypothesize that accumulation of GAS5 in the nucleus may be one of crucial processes of exerting its function. In additon, Renganathan et al revealed that GAS5 is slightly more abundant in the nucleus than that in the cytoplasm in the absence of HhAntag and prevalence in the nucleus was examined after treatment with HhAntag, indicating that HhAntag-induced growth arrest involves accumulation of nuclear GAS5 (18). This study reinforced our hypothesized model.…”
Section: Discussionsupporting
confidence: 78%
“…GAS5 was originally isolated from NIH 3T3 cells by Schneider et al with the purpose of identifying potential tumor suppressor genes enriched during growth arrest induced by serum starvation (10). GAS5 transcript levels are significantly reduced in a spectrum of cancers including breast, prostate, glioblastoma, renal clear cell, bladder, hepatocellular, pancreatic, non-small cell lung, colorectal, cervical and multiple myeloma (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Importantly, aberrant GAS5 expression was significantly correlated with metastasis in cervical cancer (21) and hepatocellular carcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNA GAS5 is non-coding, hosts multiple small nucleolar (sno) RNA sequences in its introns and contains 12 exons (27,28). GAS5 was initially identified during screening for potential tumor suppressor genes (29) and is a stress-inducible gene, which is differentially expressed in healthy and tumor tissues/cell lines (30). In addition, GAS5 has been demonstrated to be involved in the regulation of the cell cycle (31) and to function as a tumor suppressor in human T cells, and breast and prostate cancer cell lines by inducing apoptosis (10,11,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the putative open reading frame is small and poorly conserved (13,21). GAS5 is non-protein coding but its RNA is spliced, polyadenylated, and associated with ribosomes (22). The essential biological activity of GAS5 is mediated through the introns, which encode multiple snoRNAs (12).…”
Section: Structural Characterization and Biological Functions Of Gas5mentioning
confidence: 99%